Fermentative production of butyric acid from paper mill sludge hydrolysates using Clostridium tyrobutyricum NRRL B-67062/RPT 4213. (April 2018) - Liu, Siqing; Duncan, Shona; Qureshi, Nasib; Rich, Joseph
Abstract: The pulp and paper industry produces about 300–350 million tons of paper mill sludge (PMS) annually and majority is disposed of by landfill. PMS contains up to 75% carbohydrates. In this study, PMS was treated by de-ashing, fiber regeneration and enzymatic hydrolysis. The PMS hydrolysate was used for butyric acid production by Clostridium tyrobutyricum B-67062/RPT 4213. We reported that 8.52 and 8.35 gL −1 butyric acid was produced from 4 L batch fermentation in MRS and RCM4 medium respectively. Moreover, nearly 7 gL −1 butyric acid was produced by using PMS hydrolysates from two different mills when combined with a fraction of MRS, and over 6 gL −1 butyric acid was produced from hydrolysate combined with a fraction of RCM4 medium. This study suggested that beside agricultural lignocellulosic biomass feedstocks, low valued waste materials from the pulp and paper industries could also be used for the sustainable production of butyric acid.